Entrepreneurial self-efficacy on enterprise growth of SMEs in South-Eastern Nigeria: the role of entrepreneurial passion - Kusa, Nanfa Danjuma; Nson, Yilkes Danladi; Obode , Solomon (Goodwood Publishing, 2025)
Purpose: This study examines the effect of entrepreneurial self-efficacy on enterprise growth and the mediating effect of entrepreneurial passion on the relationship between entrepreneurial self-efficacy and enterprise growth of small and medium enterprises (SMES) in South Eastern Nigeria. Research Methodology: To achieve the objectives of the study, primary data were obtained using a questionnaire from a sample size of 399 SME owners in the in South Eastern States of Nigeria, comprising five States; Abia, Anambra, Ebonyi, Enugu, and Imo. The data collected were analyzed using PLS-SEM version 4. Results: The results of the analysis revealed no positive relationship between ESE and EG (? =0.198, t = 1.284, p < 0.00). A positive significant relationship exist between ESE and EP (? = 0.953, t = 149.478, 0.000). EP had a significant and positive effect on EG (? =0.470, t = 3.088, p<0.02). The mediation results revealed full mediation of EP in the relationship between ESE and EG (t = 3.093, P < 0.002). Conclusion: The study concludes that ESE alone does not directly enhance EG, but when mediated by EP, it significantly contributes to the success of SMEs. Therefore, entrepreneurial passion is essential for translating self-efficacy into enterprise growth. Limitations: The study is limited to 399 SME owners in South-Eastern Nigeria, restricting broader generalization to SMEs in other regions or contexts. Contributions: This study provides a fundamental framework for understanding the interplay between ESE, EP, and EG. This study enhances the literature by highlighting the mediating role of passion, informing policy reviews, and offering practical guidance for SME owners and entrepreneurs to strengthen growth strategies through tested entrepreneurial methods.